Ammoniacal nitrogen removal by Eichhornia crassipes-based phytoremediation : process optimization using response surface methodology - Tan, Ivy Ai Wei; Ting, Winnie Huong Tien; Shanti Faridah, Salleh; Noraziah, Abdul Wahab (Springer Nature Switzerland, 2020)
Eutrophication is a serious environmental issue that needs urgent concern. There is necessity to treat wastewater with high ammoniacal nitrogen (AN) concentration to the permissible standard limit to protect the aquatic ecosystem. This study investigated the optimum condition for AN removal from wastewater using Eichhornia crassipes-based phytoremediation process. Face-centered central composite design (CCD) was employed as the experimental design, in which four operational variables including pH (4–10), retention time (2–14 days), macrophyte density (5–30 g/L) and salinity (0–5 g NaCl/L) were involved in the study, while five responses were investigated, namely AN removal efficiency (Y1), fresh biomass growth (Y2), COD (Y3), BOD (Y4) and TSS (Y5). AN removal was the main focus in this study. Through numerical optimization, the highest AN removal efficiency of 77.48% (initial AN concentration = 40 mg/L) was obtained at the following optimum condition: pH 8.51, retention time of 8.47 days, macrophyte density of 21.39 g/L and salinity of 0 g NaCl/L. The values predicted from the models agreed satisfactorily with the experimental values, which implied that response surface methodology was reliable and practical for experimental design developed using optimization of the phytoremediation process. The validation experiment using real semiconductor effluent further supported the high potential of the E. crassipes-based phytoremediation system to remove AN and other organic pollutants in this industrial effluent under optimal condition